In situ Responses of the Eelgrass Zostera marina L. to Water Depth and Light Availability in the Context of Increasing Coastal Water Turbidity: Implications for Conservation and Restoration - Xu, Shaochun; Wang, Pengmei; Wang, Feng; Liu, Peng; Liu, Bingjian; Zhang, Xiaomei; Yue, Shidong; Zhang, Yu; Zhou, Yi (Frontiers in Plant Science, 2020)
Accelerating losses of seagrass meadows has led to efforts to restore these highly productive and beneficial ecosystems globally. Depth and light availability are critical determinants of seagrass restoration success. Eelgrass (Zostera marina L.) is the dominant seagrass species in the temperate northern hemisphere, but its global distribution has reduced dramatically. The main aims of this study were to determine: (1) the depth limit for Z. marina survival in Ailian Bay, north China, and (2) how light availability affects the growth and recruitment of Z. marina as a basis for identifying a suitable depth range for successful restoration. To achieve these aims, Z. marina shoots were transplanted from a nearby donor site, Swan Lake, to an experimental site, Ailian Bay, and the temporal responses of Z. marina shoots to light availability at water depths ranging from 1 to 8 m were investigated using in situ suspended cultures. Four suspended shoot transplantation experiments were conducted in 4 years. The results showed that the transplanted Z. marina shoots could survive and branch during an annual growth cycle, permanently underwater, at a depth ≤3 m. Due to the local turbidity of the waters in Ailian Bay, a depth of 4 m led to sufficient light deprivation (reduced to 6.48–10.08% of surface irradiance) to negatively affect seagrass shoot density and clonal reproduction. In addition, reproductive shoot density also tended to decline with water depth and light deprivation. Our results indicated that Z. marina population recruitment, through sexual and asexual (clonal growth) reproduction, were negatively affected by increasing water depth and light deprivation. These findings may provide a suitable depth range for the successful restoration of Z. marina in local coastal waters. They may also be applied to the management and restoration of Z. marina globally.